HEARING IMPAIRMENT IN CHILDREN WITH PERINATAL INJURIES OF CENTRAL NERVOUS SYSTEM - E. V. Shishkinskaya; I. A. Belyaeva; E. P. Bombardirova; N. Yu. Semenova ("Paediatrician" Publishers LLC, 2012)
The results of two-stage audiologic examination (otoacoustic emissions method and assessment of auditory evoked potentials) of 74 term and premature newborns are shown in this article. All patients received treatment for perinatal injuries of central nervous system (cerebral ischemia of various stages of severity). The assessment of brainstem auditory evoked potentials was established to be the most informative diagnostic method both in term and premature infants, moreover the majority of newborns with perinatal brain injuries had increased latencies of brainstem auditory evoked potentials parameters and signs of acoustic analyzer dysfunction, which character depended on the severity of cerebral ischemia.